Exploring the imaging features and treatment options of Mirizzi syndrome - Razi Haq, MD; Bradley Chatterton, BS; Lyle Gesner, MD (Radiology Case Reports, 2023)
The patient is a 54-year-old female who presented to the emergency department for episodic right biliary colic with nausea and vomiting over the past year. The patient's symptoms warranted multiple emergency department visits, but were self-limiting. During the most recent visit, the patient had a low-grade fever of 99.8°F (96.8°F-99.5°F) and a borderline elevated total bilirubin of 1.2 (0.2-1.2 mg/dL). Abdominal ultrasound revealed cholelithiasis, gallbladder wall thickening, and biliary ductal dilatation. Subsequent MRCP revealed an impacted stone within the gallbladder neck and a prominent common hepatic duct, compatible with Mirizzi syndrome Type I. The obtained imaging combined with clinical correlation in the setting of jaundice and right upper quadrant pain guided the patient's management. A laparoscopic cholecystectomy was performed and the patient was safely discharged the following day.